Efek Mediasi Work Engagement Dalam Pengaruh Job Characteristic Dan Perceived Organizational Support Terhadap Employee Performance Di Bidang It Pada Perusahaan Startup - Sulin dan Yanuar (Universitas Tarumanagara, 2019)
This research aims to analyze the effect between job characteristic, perceived organizational support, work engagement, and employee performance focusing in IT startup company in Indonesia. Work engagement has been theorized and proven as a mediator between its antecedents to employee performance. But very little research has been focusing on IT sector. Data are collected through questionnaire aiming at employee working in IT sector of various startup companies in Indonesia. Total sample used in this research is 389. Data analysis is conducted with Structural Equation Modelling (SEM) using AMOS software. The result of this research shows that job characteristic is significant at level 0,05 to work engagement. It is also applied to perceived organizational support with 0,05 significant level to work engagement. While their direct effects to employee performance is not significant, by the mediation of work engagement both job characteristic and perceived organizational support is significant to employee performance. This research confirms that in IT sector of startup companies in Indonesia, the effect between job characteristic and perceived organizational support to employee performance are fully mediated by work engagement.